2016
DOI: 10.14513/actatechjaur.v9.n2.403
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Speed-flow Relationship in Urban Road Traffic

Abstract: In road traffic, speed-flow curves describe the relationship between vehicle flow rates and average vehicle speeds. These functions are one of the basic elements of transport modelling and they are widely used in project appraisal. Review and re-validation of speed-flow relationship has become timely in recent years as vehicle fleet changed, average traffic volumes increased and more comprehensive, automatic data collection became available. This study used the database of the road operator in Budapest to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In order to accomplish, first and foremost the validity of the speed-flow relationship for urban routes should be clarified. It was done in another part of this research and the results can be found in another paper (see Juhász et al, 2016). The applied method and relevant consequences are summarised in the following paragraphs.…”
Section: The Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to accomplish, first and foremost the validity of the speed-flow relationship for urban routes should be clarified. It was done in another part of this research and the results can be found in another paper (see Juhász et al, 2016). The applied method and relevant consequences are summarised in the following paragraphs.…”
Section: The Methodologymentioning
confidence: 99%
“…The empirical background of the function comes from the difference between observed and modelled traffic states illustrated by Figure 3. A function that describes the conversion between observed and modelled saturation for the congested states was defined based on the VDF estimations of Juhász et al (2016). It is presented by Equation 1:…”
Section: The Methodologymentioning
confidence: 99%